Organic Fertilizer Source and Rate Determine Growth, Flower Yield, and Phytochemical Quality of Butterfly Pea on Ultisol - M. Laily Qadry Sukmana; Hilda Susanti; Gusti Rusmayadi; Zairin Zairin; Indya Dewi; Abdul Halik Setiabudi (Universitas Panji Sakti, 2026)
Butterfly pea is increasingly valued as a functional flower crop because its petals are rich in flavonoids and anthocyanins, which are used as natural colorants and antioxidants. However, production on Ultisol is frequently constrained by poor soil fertility and limited nutrient availability. This study evaluated the effects of organic fertilizer source and application rate on vegetative growth, flowering, and phytochemical quality under greenhouse conditions. The study provides an integrated factorial assessment of these response domains across contrasting organic fertilizer sources and rates on Ultisol. A 3 × 4 completely randomized factorial design with three replications compared cattle manure, poultry manure, and water hyacinth bokashi at nominal as-received rates of 5, 10, 15, and 20 t ha⁻¹. Responses included vegetative traits, flowering time, flower number, total flavonoids, and anthocyanins. Fertilizer source, application rate, and their interaction significantly affected flower number, total flavonoid content, and anthocyanin content (all P < 0.001). Poultry manure at 15 t ha⁻¹ produced 48.11 flowers plant⁻¹, 27.00 mg mL⁻¹ QE total flavonoids, and 1.65 mg 100 g⁻¹ anthocyanins; flower number was 32.0% greater than with cattle manure at the same rate. Increasing poultry manure from 15 to 20 t ha⁻¹ reduced flower number, total flavonoids, and anthocyanins by 20.1%, 43.5%, and 43.0%, respectively. Rate responses were non-monotonic and fertilizer-source-dependent. Poultry manure at 15 t ha⁻¹ was the best-performing treatment among those evaluated for balancing flower production and phytochemical quality. These findings support source-specific organic nutrient management of butterfly pea on acidic Ultisols, although multi-location field trials and nutrient-equivalent comparisons are needed before broad recommendations can be made.